Break Even Point Analysis As A Profit Planning Tool In Msmes Cv. Leilem Village Partner Era Minahasa District - hullah, abdurahman; makalalag, magdalena (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2023)
One of the planning analyses to increase profits that are expected to be used in determining the selling price of a product is through Break Even Point analysis. Through break even points, MSMEs CV. Era Mitra Desa Leilem Kabupaten Minahasa can easily determine the sales volume needed to achieve the desired level of profit. In addition, these business actors will also obtain information on the minimum level of sales that must be achieved so as not to experience losses. The purpose of this study is to analyze Break Even Point as a Profit Planning Tool in MSMEs CV. Era Mitra Desa Leilem Minahasa Regency. The research method used is a qualitative research method with a descriptive approach. Data analysis techniques begin by using content analysis, namely making transcripts of interviews, listening carefully, then writing down the words heard according to what is in the recording. The results showed that the company did not use a clear profit planning method that only followed the number of sales. In addition, in production activities in addition to lack of understanding of employees in the production process, it is also related to the shortage of raw materials that hinder the course of production. Calculation of break even point (BEP) analysis, both in units and in rupiah for the sales of furniture products, CV. Era Mitra Desa Leilem Minahasa Regency can determine the amount of profit on the sale of its products, namely after the sale of 219 units or after obtaining a sales value in rupiah of Rp366,825,000,-. If in 2022 CV. Era Mitra Desa Leilem, Minahasa Regency wants profit to increase by Rp5,000,000 from the profit of the previous period, so the expected amount of profit is Rp65,000,000 CV. Era Mitra Desa Leilem Minahasa Regency had to sell its furniture products as many as 861 sets.